기업결합 규제에서의 효율성 및 파산기업 항변: 경제적 논거와 정책적 함의 - 진양수 (12969, 2013)
This paper provides consistent understanding between the economic rationale of the ‘efficiency’ and ‘failing firm’ defenses and the conditions that the defenses require in the merger assessment process, focusing on two main concepts, ‘enhancing compe